MoS, rGO, and CuO Nanocomposite-Based High Performance UV-Visible Dual-Band Photodetectors - Singh R.; Jit S.; Tripathi S. (My University, 2025)
This letter reports a Pd/MoS2/rGO/CuO/ITO structure based Metal-Semiconductor-Metal (MSM) photodetector. The proposed MSM device is obtained by vertical integration of a Pd/MoS2 Schottky junction and a CuO /ITO (i.e., (Indium-doped Tin Oxide) Schottky junction separated by thin reduced graphene oxide (rGO) layer. The rGO layer is used to improve the quality of the MoS2 layer by mitigating the effects of both the lattice mismatching and van der Waals gap between the MoS2 (Molybdenum disulphide) and CuO (Copper Oxide) layer. The proposed photodetector shows a UV-Visible dual-band photoresponse when the device is illuminated by a monochromatic light intensity of 13.6~\mu W/cm2 at different wavelengths over 300-800 nm. Excellent responsivities and detectivities of 646.8 A/W and 7.28\times 10 ^{14} Jones at 300 nm (in the UV region) and; of 84.32 A/W and 9.6\times 10 ^{13} Jones at 498 nm (in the visible region) are measured at 1 V bias voltage, respectively. Also, the device also shows exceptionally high external quantum efficiency (EQE) of 2.6\times 10 ^{5} % and 3.7\times 10 ^{4} % at 300 nm and 498 nm, respectively. © 1989-2012 IEEE.